PRUDENCE ACCOUNTING: THE ROLE OF FINANCIAL DISTRESS, FREE CASH FLOW, AND CAPITAL INTENSITY IN ACCOUNTING DECISIONS - Warhaeti, Heti; Rahmawati, Teti; Purnama, Dendi (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
The Study analyzes the influence of financial distress, free cash flow, and capital intensity on prudent accounting. The research methods used are descriptive and verification methods. The population in this research is the 57 metal & mineral mining subsector companies listed on the Indonesia Stock Exchange in 2019-2022. The final sample was obtained from as many as 46 companies through the purposive sampling method, where the research was conducted for four years. The data collection technique used was non-participant. The analysis technique used is panel data regression analysis. The research results show that financial distress, free cash flow, and capital intensity influence accounting prudence. Economic distress, free cash flow, and capital intensity significantly positively affect prudence accounting.